PENGARUH KOMUNIKASI DAN KUALITAS KEHIDUPAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN UNIT PELAYANAN PUBLIK BADAN NASIONAL PENEMPATAN DAN PERLINDUNGAN TENAGA KERJA INDONESIA (BNP2TKI) - Setyoningrum, Dika Putri; Diphojoyo, Gede Umbaran (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2019)
This research is a quantitative study that aims to examine the effect of communication with work satisfaction, quality of work life with job satisfaction and communication and quality of work life with job satisfaction. The subjects in this study were employees of the BNP2TKI public service unit with a total of 40 samples, using census sampling techniques. This study uses 3 scale measuring instruments, namely: work satisfaction scale, communication scale and quality of work life scale. The results of this study indicate that there is a significant influence between communication with job satisfaction with r = 0.435. There is a significant influence between the quality of work life with job satisfaction with r = 0.703. There is a significant influence between communication and quality of work life on job satisfaction with R₂ = 0.617 or 61.7%. This shows that the alternative hypothesis (Ha3) in this study was accepted. Quality of work life accounted for 0.481 or 48.1% greater than communication which contributed 0.123 or 12.3% and 40.3% were other factors not examined by researchers.